The Performance of the Uterine Artery Resistance Index following Stimulation of the Cervix in the Diagnosis of Endometriosis: A Prospective Study - Su-Hong Jia; Hong Sun; Ying Wei; Qi Ma; Qiong-Zhen Ren; Min-Fang Shao; Yu-Ma Jin; Yuan Xie (Clinical and Experimental Obstetrics & Gynecology)
Background: We speculated that stimulating the uterine cervix of patients may increase blood flow resistance of the uterine artery more significantly in women with endometriosis than those without. Accordingly, the resistance index (RI) of the uterine artery following stimulation of the cervix may offer a novel and promising non-invasive method for diagnosing endometriosis. In this prospective study, the aim was to determine the performance of the uterine artery resistance index (RI) following stimulation of the cervix in the diagnosis of endometriosis. Methods: This prospective cohort study included 270 patients with non-uterine diseases who were scheduled for laparoscopic surgery. Each patient underwent Doppler sonography for peak systolic velocity (PSV), end diastolic velocity (EDV), and RI before and after stimulation of the cervix, in addition to conventional ultrasound examination one day prior to laparoscopic surgery. The cervix was stimulated using a double convex array electronic vaginal probe for real-time tissue elastography. Results: Laparoscopic surgical evaluation revealed endometriosis in 91 (33.7%) patients. Following stimulation of the cervix, the RI of the uterine artery was significantly increased in the endometriosis group (p = 0.00), but no significant increase in the RI was observed in the control group (p = 0.45). The sensitivity and specificity of the post-stimulation RI for diagnosing endometriosis (using a cut off of 0.83) were 85.71% (95% confidence interval (CI): 76.45–91.88) and 88.83% (95% CI: 83.05–92.87), respectively. For peritoneal endometriosis (PEM), sensitivity and specificity were 86.96% (95% CI: 65.33–96.57) and 88.83% (95% CI: 83.05–92.87), respectively. The sensitivity and specificity of transvaginal ultrasonography (TVU) for diagnosing endometriosis were 63.74% (95% CI: 52.93–73.37) and 94.41% (95% CI: 89.68–97.14), respectively. The positive rate for TVU in diagnosing all endometrioses was 63.7%, and this was lower than that for the post-stimulation RI (84.6%, p = 0.001). Conclusions: Stimulation of the cervix leads to a significant decrease in uterine blood perfusion in women with endometriosis. TVU is a sensitive and specific method for the diagnosis of endometrioma, while the RI is a more sensitive parameter for diagnosing PEM than TVU. For the diagnosis of endometriosis, especially for PEM, the post-stimulation RI may prove to be a promising non-invasive diagnostic technique.